ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN PERAWAT MENGGUNAAN ALAT PELINDUNG DIRI (HANDSCOON) DI RSUD BENDAN KOTA PEKALONGAN - Darmawati .; M. Projo Angkasa; Isrofah . (LPPM Universitas Pekalongan, 2015)
Personal protective equipment is a part of the hazard control in the workplace that should always be used to ensure safety, especially in the use of handscoon when the nurse injected a patient in the hospital.This research was aimed to determine the factors that affect nurse’s compliance to the use of personal protective equipment (handscoon) when giving injection in patient rooms of RSUD Bendan Pekalongan city.This study used a croos – sectional approach with a total sampling technique of 98 respondents.The result showed that the majority of respondents were 31 - 35 years old (35 respondents), female (53 respondents), have been working for 3 - 4 years (55 respondents), and D3 - educated (58 respondents) as many as 35,7 % ; 54,1 % ; 56,1 %, and 5,2 %respectively. The majority of respondents (55,1 %) had a good knowledget. However 56,1 % respondents had a poor attitude toward. A total of 55 respondents (56,1%) stated that the availability of personal protective equipment in the hospital was less complete. A total of 68 people (69,4 %) stated that the personal protective equipment in the hospital was less convenient to use. As many as 59respondents (60,2 %) stated that the rules of personal protective equipment in the hospital was less well. Supervision of personal protective equipment also was stated less well by 74 respondents (75,5 %), and the majority of respondents (72,4 %) complied with the use of personal protective equipment when giving an injection to a patient in the inpatient rooms at RSUD Bendan Pekalongan city.This study concluded that there was influence of the availability of personal protective equipment, attitude toward, and regulation of personal protective equipment and attitude toward with nurse’s compliance in the use of personal protective equipment (handscoon) when giving injection to a patients in the patient rooms at RSUD Bendan Pekalongan city.Keywords : Factors affecting compliace, personal protective equipment and Injection.